TANGGUNG JAWAB DIREKSI BERDASARKAN PRINSIP FIDUCIARY DUTIES DALAM PERSEROAN TERBATAS - Ratih Purwantari, Putu; Mahartayasa, Made (Kertha Semaya : Journal Ilmu Hukum, 2014)
The Board of Director is the main part of business that ensures its continuity because the company cannot do anything without the role of board members. The relationship between members of board and company aside from work, members of board has also a fiduciary relationship (trust) with the company. The issue raised is about The Responsibilities of Board Members Based on Fiduciary Principle in Incorporated Company. The method used on this paper is normative method which is descriptive namely by reviewing the materials as consideration on drawing conclusions. The analysis is done by studying the responsibilities of board members based on Fiduciary Duties principle in incorporated company. The conclusion of this paper is The Responsibilities of Board Members Based on Fiduciary Principle in Incorporated Company is the directors must be able to carry out their duties with full good faith, responsibility, and avoid any conflict of interest. Directors are also required to act with caution in making all decisions and policies (duty of care) as well as being able to put his personal interests above the interests of the company (duty of loyalty).
Keywords: Director, Fiduciary Duties, Incorporated Company